Forced degradation of tacrolimus and the development of a UHPLC method for impurities determination - Peterka Tanja Rozman; Lušin Tina Trdan; Bergles Jure; Ham Zoran; Grahek Rok; Urleb Uroš (Acta Pharmaceutica)
An ultra-high performance liquid chromatography method for simultaneous determination of tacrolimus impurities in pharmaceutical dosage forms has been developed. Appropriate chromatographic separation was achieved on a BEH C18 column using gradient elution with a total run time of 14 min. The method was applied to analyses of commercial samples and was validated in terms of linearity, precision, accuracy, sensitivity and specificity. It was found to be linear, precise and accurate in the range of 0.05 to 0.6 % of the impurities level in pharmaceutical dosage forms. Stability indicating power of the method was demonstrated by the results of forced degradation studies. The forced degradation study in solution revealed tacrolimus instability under stress alkaline, thermal, light and photolytic conditions and in the presence of a radical initiator or metal ions. The drug was stable at pH 3–5. Solid-state degradation studies conducted on amorphous tacrolimus demonstrated its sensitivity to light, elevated temperature, humidity and oxidation.